Characterization Of Acinetobacter Sp. Lwc1 Isolated From Contaminated Water And Its Survivability Under Different Stress Condition - Lim, Wui Chen (2014)

(untitled)
The role of PHA in the survival of bacteria in contaminated waters was investigated in this study. This study began with the isolation of a bacterium from water contaminated with domestic wastes, followed with the identification and characterization of the isolate and ended with the stress treatments to it. Peranan PHA dalam kemandirian bakteria di dalam air yang tercemar telah diselidik dalam kajian ini. Eksperimen ini bermula dengan pemencilan bakteria daripada air yang telah dicemari dengan sisa domestik, diikuti dengan pengenalan dan pencirian bakteria tersebut dan diakhiri dengan rawatan tekanan terhadapnya.